A Penny for Your Thoughts: Children’s Inner Speech and Its Neuro-Development - Geva, Sharon; Fernyhough, Charles (Frontiers in Psychology, 2019)
Inner speech emerges in early childhood, in parallel with the maturation of the dorsal language stream. To date, the developmental relations between these two processes have not been examined. We review evidence that the dorsal language stream has a role in supporting the psychological phenomenon of inner speech, before considering paediatric studies of the dorsal stream’s anatomical development and evidence for its emerging functional roles. We examine possible causal accounts of the relations between these two developmental processes, and consider their implications for phylogenetic theories about the evolution of inner speech and the accounts of the ontogenetic relations between language and cognition.